Respuestas

¡La mejor respuesta!
  • Usuario de Brainly
2013-03-10T19:00:04+01:00

simplifica

 

\frac{\frac{c+d}{c}}{\frac{c-d}{2c}}=\frac{2c(c+d)}{c(c-d)}=\frac{2(c+d)}{c-d}

 

yo creo que es todo lo que se puede simplificar. 

 

Saludos.

  • Usuario de Brainly
2013-03-10T20:01:50+01:00

c+d

-------

..c................2c(c+d)

---------- =-------------------= simplificando

c -d.................(c-d).c

-------

2c

 

c(c+d)

----------- = resultado final

(c -d)

 

espero que te sirva, salu2!!!